Synergistic exposure of rice seeds to different doses of gamma-ray and salinity stress resulted in increased antioxidant enzyme activities and gene-specific modulation of TC-NER pathway - Macovei, Anca; Garg, Bharti; Raikwar, Shailendra; Balestrazzi, Alma; Carbonera, Daniela; Buttafava, Armando; Bremont, Juan Francisco Jiménez; Gill, Sarvajeet Singh; Tuteja, Narendra (Hindawi Limited, 2014)
Recent reports have underlined the potential of gamma (γ)-rays as tools for seed priming, a process used in seed industry to increase seed vigor and to enhance plant tolerance to biotic/abiotic stresses. However, the impact ofγ-rays on key aspects of plant metabolism still needs to be carefully evaluated. In the present study, rice seeds were challenged with different doses ofγ-rays and grown in absence/presence of NaCl to assess the impact of these treatments on the early stages of plant life. Enhanced germination efficiency associated with increase in radicle and hypocotyl length was observed, while at later stages no increase in plant tolerance to salinity stress was evident. APX, CAT, and GR were enhanced at transcriptional level and in terms of enzyme activity, indicating the activation of antioxidant defence. The profiles of DNA damage accumulation were obtained using SCGE and the implication of TC-NER pathway in DNA damage sensing and repair mechanisms is discussed.OsXPB2,OsXPD,OsTFIIS,andOsTFIIS-likegenes showed differential modulation in seedlings and plantlets in response toγ-irradiation and salinity stress. Altogether, the synergistic exposure toγ-rays and NaCl resulted in enhanced oxidative stress and proper activation of antioxidant mechanisms, thus being compatible with plant survival.